SYSTEMIC PROBLEMS OF THE RUSSIAN FOREIGN TRADE POLICY - G. M. Bystrov (Russian Journal of Economics and Law)
The article is devoted to the issues of correlation between liberalization and protectionism in trade policy from the point of view of systemic reforms in the Russian economy.